Wspomnienia pracownikow Rozglosni Polskiej Radia Wolna Europa - Grabowska, Alina (Warszawa : Oficyna Wydawnicza Rytm, 2002)
A collection of personal accounts from the workers at Radio Free Europe in Poland.
Keywords: Radio Free Europe -- History; Radio Free Europe. -- Polish Service; Radio broadcasting -- Poland -- History